Crystallization Kinetics of Alkali Feldspar in Peralkaline Rhyolitic Melts: Implications for Pantelleria Volcano - Arzilli, Fabio; Stabile, Paola; Fabbrizio, Alessandro; Landi, Patrizia; Scaillet, Bruno; Paris, Eleonora; Carroll, Michael R. (Frontiers in Earth Science, 2020)
Peralkaline rhyolites, associated with extensional tectonic settings, are medium to low viscosity magmas that often produce eruptive styles ranging from effusive to highly explosive eruptions. The role of pre-eruptive conditions and crystallization kinetics in influencing the eruptive style of peralkaline rhyolitic magmas has been investigated and debated considering equilibrium conditions. However, experimental constraints on the effect of disequilibrium in crystallization in such magmas are currently lacking in the literature. Therefore, we performed isobaric cooling experiments to investigate alkali feldspar crystallization kinetics in peralkaline rhyolitic melts. Experiments were performed under water-saturated, water-undersaturated and anhydrous conditions between 25 and 100 MPa, at 670-790 °C and with experimental durations ranging from 0.5 to 420 hours. Here we present the first data on crystallization kinetics of alkali feldspar, which is the main crystal phase in peralkaline rhyolitic melts, in order to improve our understanding of the evolutionary timescales of these melts and their ability to shift between effusive and explosive activity. Our experimental results indicate that the alkali feldspar nucleation delay can range from hours to several days as a function of undercooling and H2O content in the melt. Thus, a peralkaline rhyolitic magma can be stored at the pre-eruptive conditions for days without important variations of its crystal fraction. This suggests that crystallization may not necessarily play the main role in triggering fragmentation during explosive eruptions of peralkaline rhyolitic magmas.